Statin therapy and outcome in Takotsubo syndrome patients: results from the multicenter international GEIST registry - Novo, Giuseppina; Arcari, Luca; Stiermaier, Thomas; Alaimo, Chiara; El-Battrawy, Ibrahim; Cacciotti, Luca; Guerra, Federico; Musumeci, Beatrice; Mariano, Enrica; Parisi, Giuseppe; Montisci, Roberta; Vazirani, Ravi; et al. (Atherosclerosis, 2024)
Background and aims - Several studies have shown that endothelial dysfunction plays a role in the pathogenesis of Takotsubo syndrome (TTS). Given the potential benefit of statin therapy on endothelial dysfunction, we hypothesized that such treatment could improve outcome. Aim of our study was to evaluate clinical characteristics and outcome of TTS patients treated with statin therapy. - Methods - Patients were enrolled in the international multicenter GEIST (GErman Italian Spanish Takotsubo) registry. Demographic data, clinical features and drug therapy at discharge were recorded. Primary study outcome was the occurrence of all-cause death at follow-up. - Results - Study population included 2429 consecutive TTS patients: 1293 (53.2%) discharged on statin and 1136 (46.8%) without statin. Patients with statin were older (age 72 ± 11 vs 69 ± 13 years, p < 0.001), with higher prevalence of hypertension (74.3% vs 60.3%, p < 0.001), diabetes (21.1% vs 14.7%, p < 0.001), dyslipidemia (56.1% vs 23.3%, p < 0.001), history of coronary artery disease (13.3% vs 6.3%, p < 0.001) and lower rates of in-hospital complications (14.7% vs 19.3%, p = 0.003). Survival analysis showed similar mortality rates between groups (log rank p = 0.803). At univariable analysis, statin therapy at discharge was not associated with lower mortality (HR: 0.97, 95% CI 0.74-1.26, p = 0.803). At multivariable analysis age (HR: 1.06 95% CI 1.04-1.08, p < 0.001), male sex (HR: 1.83, 95% CI 1.20-2.80, p = 0.005), diabetes (HR: 2.55, 95% CI 1.83-3.54 p < 0.001), malignancies (HR: 2.41, 95% CI 1.68-3.44, p < 0.001) and physical trigger (HR: 2.24, 95% CI 1.62-3.10, p < 0.001) were associated with increased mortality. - Conclusions - Statin therapy after a TTS event was not associated with better prognosis at follow-up.
Online verfügbar: 13. Dezember 2023, Artikelversion: 21. Dezember 2023
Gesehen am 22.03.2024